Recombinant human adenovirus type 5 administration for the treatment of malignant ascites or pleural effusion in cancer patients: a meta-analysis - Duan, Changsong; Liu, Xue (Frontiers in Oncology, 2025)
ObjectiveH101 (recombinant human adenovirus type 5) has favorable efficacy and safety in cancer patients with malignant ascites (MA) or pleural effusion (MPE). However, a comprehensive evaluation has not yet been conducted. This meta-analysis aimed to comprehensively investigate the efficacy and safety of H101 in these patients.MethodsThe meta-analysis was registered on PROSPERO (ID: CRD420251052407). A comprehensive study search was conducted in PubMed, Web of Science, Cochrane Library, Wan Fang, CNKI, and SinoMed until October 2024. Studies reporting on the remission and safety results in cancer patients with MA/MPE treated with H101 were screened. The overall remission rates (ORRs) of ascites or pleural effusion and adverse reactions were analyzed.ResultsA total of 13 studies involving 993 patients were included. The pooled ORR was 69.9% (95%CI = 63.5%–76.4%). The pooled rates of fever, nausea or vomiting, and leukopenia were 22.5% (95%CI = 10.2%–34.9%), 14.0% (95%CI = 6.8%–21.2%), and 24.3% (95%CI = 9.6%–39.1%), respectively. Subgroup analysis revealed that the ORR was higher in studies with a single cancer type than in those with multiple cancer types (p = 0.012). There was no publication bias in the ORR, the rate of nausea or vomiting, or the rate of leukopenia. The publication bias in the rate of fever was corrected using the trim-and-fill method, and the adjusted rate was 5.4% (95%CI = 0.0%–22.0%). All of the included studies were of high-quality, with a low risk of bias. The sensitivity analysis revealed high robustness of the results.ConclusionH101 is effective and safe for the treatment of MA/MPE in patients with cancer and may be a promising modality for their clinical management.